Pengaruh Persepsi Layanan Publik terhadap Migrasi di Indonesia - Husna, Mudhiah Maya; Djamaluddin, Sartika (Jurnal Informatika Ekonomi Bisnis, 2024)
Population mobility occurs every day. Many factors encourage individuals to make the movement. In addition to economic driving factors, social factors such as public services also influence individual decisions to migrate. Regions with good quality public services will trigger migration growth. The quality of public services is assessed on individual perceptions. This research focuses on 4 (four) perceptions of public services, namely perceptions of transportation services, perceptions of education services, perceptions of health services, and perceptions of business license services. The test was carried out using the Random Effect Probit Regression method. We find that perceptions of transportation services, education and business permits have a significant effect on migration.